새마을운동 참여도에 미치는 영향요인에 관한 연구 - 이미숙(Mi-Sook Lee) (한국비교정부학보, 2012)
The purpose of this study is to explore the influential factors in the intention of SAEMAUL UNDONG participation. To reveal the factors effecting on the participation, this study used a structural equation modeling(SEM) analysis by using the SPSS win 12.0 and AMOS 18.0 which is powerful tool analyzing the causes and effects relationship between variables. The results of this research indicate that the degree of SAEMAUL UNDONG participation is effected by the previous experiences and the community attachment. These results meant that the more the villagers take part in the SAEMAUL UNDONG activities in previous time and the stronger the villagers are showing the community ties, it gets the higher the intention of SAEMAUL UNDONG participation. The results of multi-group comparison analysis showed that the community leader group has more important influential impacts on the participation than the normal community members have ones. The results of this study suggested to promote the SAEMAUL UNDONG participation. First, expand the opportunities to involve the SAEMAUL UNDONG activities among the community members, second, enhance the feeling of community attachment, third, apply the differentiated strategies to the group of community leaders as a policy partner and to the normal community members by attracting interests in community affairs, and fourth, continue the suitable education programs for the community members to make understand the SAEMAUL UNDONG and collaboration for the participation. KCI Citation Count: 10